2019
DOI: 10.4103/ijnm.ijnm_70_19
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of intraoperative frozen section of the sentinel lymph node in the management of early-staged oral tongue cancers

Abstract: Background:The present study aims to explore the role of sentinel lymph node biopsy (SLNB) with intraoperative frozen section in the management of early-staged oral tongue cancers.Materials and Methods:Fifty-two patients with clinical stages cT1/2N0 oral tongue cancers were included in the present study. The curative surgery was preceded by the performance of an SLNB using a dual technique.Results:The identification rate of sentinel lymph node (SLN) in this study was 98.07%. The sensitivity, specificity, posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Two authors individually collected data from included articles in forms commensurate with each other. Diagnostic accuracy, represented by DOR, summary receiver operating characteristic (SROC) curve, and area under the curve (AUC), was calculated 1,5,11–102 . DOR was calculated as (true positive [TP]/false positive [FP])/(false negative [FN]/true negative [TN]) to assess diagnostic accuracy with 95% confidence intervals (CIs).…”
Section: Methodsmentioning
confidence: 99%
“…Two authors individually collected data from included articles in forms commensurate with each other. Diagnostic accuracy, represented by DOR, summary receiver operating characteristic (SROC) curve, and area under the curve (AUC), was calculated 1,5,11–102 . DOR was calculated as (true positive [TP]/false positive [FP])/(false negative [FN]/true negative [TN]) to assess diagnostic accuracy with 95% confidence intervals (CIs).…”
Section: Methodsmentioning
confidence: 99%
“…With regard to quality-oflife outcomes, Garrel et al 2 reported significantly improved neck and shoulder function in the SLNB group compared with the END group up to their 2-year analysis, at which time point there was no statistical difference. We await the outcome of NRG-HN006 5 to confirm these findings definitively, although reporting on survival outcome is not likely to be available until the next decade.…”
Section: Sentinel Node Biopsy In Oral Cancer-indications Analysis And...mentioning
confidence: 97%
“…Some studies have suggested that SLNB frozen section is not as effective for identifying micromestases, 4 while others have found that it changes management in 71% of cases, avoiding a second operation and expediting care. 5 False-negative rates from frozen section have been reported to be as low as 7%, but this is in the context of multislice frozen section as opposed to a simple bisection technique. 6 While variability may exist in how the specimen is processed, many clinicians continue to use frozen section during SLNB for oral cavity cancer to avoid a second procedure.…”
Section: Clarementioning
confidence: 99%
See 1 more Smart Citation
“…With regard to quality-oflife outcomes, Garrel et al 2 reported significantly improved neck and shoulder function in the SLNB group compared with the END group up to their 2-year analysis, at which time point there was no statistical difference. We await the outcome of NRG-HN006 5 to confirm these findings definitively, although reporting on survival outcome is not likely to be available until the next decade.…”
Section: Sentinel Node Biopsy In Oral Cancer-indications Analysis And...mentioning
confidence: 97%